Prospects for anticipating kidney damage in type-2 diabetes patients through the sensing of albumin passing through the renal glomerulus - Nieto Chaupis, Huber (2017)
In this paper, we explore the prospects of applicability for the sensing of proteins inside the framework of the IoB NT [1] for anticipating the diabetes kidney disease (DKD), from the identification of negatively charged proteins of albumin which are already passing the glomerular layers located in the kidney. The expected high efficiency of the interfaces between the biochemical domains and the standard electromagnetic networks devices might guarantee a continuous surveillance that aims to identify in time, the beginning of abnormal functionality of kidneys through a dedicate sensing of albumin. Concretely, we focus in the detectability of albumin considering its main noise given by the Tamm-Horsfall's proteins. Our simulations have encountered that the efficiency for sensing of albumin passing the glomerulus might be at least of order of 60% ± 5%.